Optimization of Thermodynamic Properties of R134a Vehicle Air Conditioning System with Internal Heat Exchanger - Yue Zhenyu; Chen Huanxin; Zhong Chang (Zhileng xuebao)
In theory, using internal heat exchanger in the R134a vehicle air conditioning system can improve the cooling performance significantly，but many experimental studies demonstrates that the internal heat exchanger has a negative effect on the safety of the system. Therefore the advantage and the disadvantage trade off, which makes the merit not conspicuous. Aimed at this situation, the influence of different length of internal heat exchanger on the air conditioning system comprehensive performance is investigated in test bench in this paper. It shows that the adverse effects have certain relationships with the tube length on the basis of the experiments. In addition, this study also obtain a method to avoid adverse effects, by adjusting the expansion valve, condenser air flow and oil, which provides theoretical foundation for the matching of heat regeneration system.